FEATURES OF APPLICATION OF GRAPHS FOR THE ANALYSIS OF INFORMATION FLOWS - V. V. Savluchinskij (Системный анализ и прикладная информатика)
In connection with the increase of information confrontation leading States you need to substantiate the possibility to predict real conflicts, including military, observing the information flows generated by media information. Besides the analysis of the results obtained in monitoring the flow of information requires a mathematical evaluation of the studied processes in the information field and forming conclusions on prospects of development of these information flows. Approach to the solution of this problem is given in the article.The main difficulty in processing information messages, provided to the media for any thematic focus are their almost unlimited quantities. Currently, there are various search engines, allowing for a specific set of keywords you specify any search depth informational messages, surveys, analytic studies for hyperlinks. However, redraft the proposed huge volumes of Internet information resources and to issue its own version requires time-consuming, sometimes not commensurate with the urgency of the generated document. As a result on the Internet is taken, as a rule, ready to stamp the appropriate under preference analytics produces an information document, which suffers from objectivity in the conclusions and assessments.